Topical tacrolimus for the treatment of secondary lymphedema - Jason C. Gardenier (Nature Portfolio, 2017)
Secondary lymphedema is a debilitating disease with no cure. Here the authors show that topical application of an FDA-approved anti-T cell drug tacrolimus potently prevents development and alleviates pathologic changes of established lymphedema in mice, suggesting a new treatment for human patients.